Dini musiki uygulamalarının hafif zihinsel engelli çocukların öz saygısına olan etkisi - Özsağır, Abdurahman (My University, 2017)
DİNİ MUSİKİ UYGULAMALARININ HAFİF ZİHİNSEL ENGELLİ ÇOCUKLARIN ÖZ SAYGISINA OLAN ETKİSİ Bu çalışmanın amacı dini musiki uygulamalarının hafif zihinsel engelli çocukların

saygısına olan etkisini incelemektir. Bu amaçla İstanbul, Ümraniye’ de bulunan Özel Rota Özel Eğitim ve Rehabilitasyon Merkezi’nde eğitim gören 33 hafif zihinsel engelli öğrenci seçilmiş ve bu öğrencilerle 8 hafta boyunca dini musiki çalışması yapılmıştır. Araştırma da ön test son test kontrol grupsuz desen kullanılmıştır. Araştırmada elde edilen sonuçlara göre verilen eğitim sonunda dini musiki uygulamalarının hafif zihinsel engelli çocukların öz saygına her ne kadar cinsiyet, yaş, ailedeki çocuk sayısı, çocuğun doğum sırası, ailenin gelir düzeyi gibi faktörlerin etkisi olmasa da; ailenin eğitim düzeyi ve genel olarak öz benlik saygısı oranındaki kayda değer yükseliş dikkat çekicidir ve anlamlı bir farklılık vardır.According to the our results, although the religious music practices are not affected by variables such as gender, age, number of children in the family, birth order of the child, income level of the family, self-esteem of children with mild mental retardation. The level of education of the family and the overall increase in the self-esteem ratio is noteworthy. In other words, there is a statistically significant difference between level of education of the family and self esteem of children with mild mental retardation. zel Eğitim, Hafif Zihinsel Engelli Çocuklar, Benlik Saygısı ABSTRACT THE EFFECTS OF RELIGIOUS TURKISH MUSIC APPLICATIONS TO SELF-ESTEEM ON CHILDREN WITH MILD MENTAL RETERDATION The purpose of this research is to examine the effects of religious Turkish music applications to self-esteem on children with mild mental retardation. For this purpose, it is chosen 33 children with mild mental retardation from rehabilitation center in Umraniye, İstanbul and it is done a musical activities and event during eight (8) weeks. Also, it is used pretest and post test design research in this thesis. According to the our results, although the religious music practices are not affected by variables such as gender, age, number of children in the family, birth order of the child, income level of the family, self-esteem of children with mild mental retardation. The level of education of the family and the overall increase in the selfesteem ratio is noteworthy. In other words, there is a statistically significant difference between level of education of the family and self esteem of children with mild mental retardation.Religious Music, Special Education, Self Esteem
Keywords: Benlik Saygısı Religious Music; Dini müzik; Hafif Zihinsel Engelli Çocuklar; Özel Eğitim; Pisikolojik yönler; Psikolojik yönler; Self Esteem; Special Education; Zihinsel engelli çocuklar